Wind environmental evaluation of neighborhood areas in major towns of Malaysia - Kubota, Tetsu; Ahmad, Supian (2006)
This paper discusses planning guidelines of neighborhood residential areas in consideration of wind flow in Malaysia. It aims to reduce the energy consumption particularly from the use of air-conditioners. Wind flow at the neighborhood level has a large potential to promote natural ventilation in each dwelling unit. This paper reports results of the wind environmental evaluation of case study areas under respective climatic conditions in major towns of Malaysia. The results showed that the calculated mean wind velocities in most terraced houses cases did not meet required criterion under respective climatic conditions in the east coast towns and inland town of Peninsular Malaysia. This was mainly due to the weak wind conditions in these towns. It was considered that the location of towns, i.e. distance from the coastal line, had significant influence on such weak wind conditions. This paper finally suggested that the high-rise housing could be one of the effective means to utilize higher wind at the elevated floor level under weak wind conditions in urban Malaysia.